Sex- and age-specific associations between major depressive disorder and metabolic syndrome in two general population samples in Germany. (16th November 2016) - Block, Andrea; Schipf, Sabine; Van der Auwera, Sandra; Hannemann, Anke; Nauck, Matthias; John, Ulrich; Völzke, Henry; Freyberger, Harald Jürgen; Dörr, Marcus; Felix, Stephan; Zygmunt, Marek; Wallaschofski, Henri; et al.
Abstract: Background and aims: Major depressive disorder (MDD) has been associated with the Metabolic Syndrome (MetS). As previous data strongly suggested sex and age effects on this association, this study aimed to analyse the association between MDD and MetS in two general population samples under explicit consideration of sex and age. Methods: This study analysed cross-sectional data based on two independent general population samples: SHIP-0 ( n  = 4083; 20–81 years; 49.4% male) and SHIP-TREND-0 ( n  = 3957; 20–83 years; 49.0% male) that were part of the Study of Health in Pomerania. MDD (SHIP-0: 12.6%; SHIP-TREND-0: 27.2%) was assessed using the Composite International Diagnostic-Screener (CID-S) in both samples. Interview assessment of MDD diagnosis according to Diagnostic and Statistical Manual of Mental Disorders IV (DSM-IV) criteria was performed in SHIP-TREND-0 (18.1% MDD). MetS was defined by abdominal obesity, elevated blood pressure, elevated glucose, elevated triglycerides and reduced high-density lipoprotein cholesterol according to established criteria. Data analysis was performed sex- and age-stratified. Results: Prevalence of MetS was high in both samples: 19.4% of females and 30.2% of males in SHIP-0 and 22.1% and 33.2% in SHIP-TREND-0, respectively. Effect modifications were observed by sex and age on the association between MDD and MetS. Particularly, younger females (20–49 years) with MDD were more often affected by MetS than younger females without MDD: OR = 2.21 (95% CI = 1.39–3.50). This association vanished in elderly participants (50–82 years). Conclusion: The data suggest that especially younger (presumably pre-menopausal) females with MDD are more likely to have MetS than those without major depressive disorders, and that age extenuates this association.